Death and bereavement across cultures - Parkes, Colin Murray; Laungani, Pittu; Young, Bill, 1959- (London ; New York : Routledge, Taylor & Francis Group, 2015)
'All societies have their own customs and beliefs surrounding death. In the West, traditional ways of mourning are disappearing, and although Western science has had a major impact on how people die, it has taught us little about the way to die or to grieve. Many whose work brings them into contact with the dying and the bereaved from Western and other cultures are at a loss to know how to offer appropriate and sensitive support. Death and Bereavement Across Cultures 2nd Edition is a handbook which meets the needs of doctors, nurses, social workers, hospital chaplains, counsellors and volunteers caring for patients with life-threatening illness and their families before and after bereavement. It is a practical guide explaining the religious and other differences commonly met with in multi-cultural societies when someone is dying or bereaved. In doing so readers may be surprised to find how much we can learn from other cultures about our own attitudes and assumptions about death. Written by international experts in the field the book: - Describes the rituals and beliefs of major world religions; - Explains their psychological and historical context; - Shows how customs are changed by contact with the West; - Considers the implications for the future The second edition includes new chapters that: explore how members of the health care professions perform roles formerly conducted by priests and shamans, can cross the cultural gaps between different cultures and religions; consider the relevance of attitudes and assumptions about death for our understanding of religious and nationalist extremism and its consequences; discuss the Buddhist, Islamic and Christian ways of death'--
pt. I.A conceptual framework: historical and cultural themes -- 1. Introduction / Colin Murray Parkes, Pittu Laungani and Bill Young -- 2. Culture and religion / Colin Murray Parkes, Pittu Laungani and Bill Young -- pt. II. Major world systems of belief and ritual -- 3. Grief in small scale societies / Paul C. Rosenblatt -- 4. Death in a Hindu family / Pittu and Ann Laungani -- 5. The Buddhist way of death / Margaret Gouin -- 6. Jewish views and customs on death / Ellen Levine -- 7. Christianity: beliefs and practices about death and bereavement / Peter C. Jupp -- 8. The Islamic way of death and dying: homeward bound / Waseem Alladin -- 9. Secularisation / Tony Walter -- pt. III. Practical implications and conclusions -- 10. Childhood death and bereavement across cultures / Danai Papadatou -- 11. Help for the dying and the bereaved / Colin Murray Parkes -- 12. Conclusions I: implications for practice and policy / Pittu Laungani, Colin Murray Parkes and Bill Young -- 13. Conclusions II: attachments and losses in cross-cultural perspective / Colin Murray Parkes.
Includes bibliographical references and index.
Keywords: Attitude to Death; Bereavement; Cross-cultural comparison